A comparative experimental and theoretical investigation of hydrogen‐bond, halogen‐bond and π–π interactions in the solid‐state supramolecular assembly of 2‐ and 4‐formylphenyl arylsulfonates. Issue 7 (11th June 2018) - Andleeb, Hina; Khan, Imtiaz; Bauzá, Antonio; Tahir, Muhammad Nawaz; Simpson, Jim; Hameed, Shahid; Frontera, Antonio
Abstract : A series of solid‐state structures of 2‐ and 4‐formylphenyl 4‐substituted benzenesulfonates were investigated. Remarkably, halogen‐bonding interactions are found to be important to rationalize their solid‐state crystal structures. Abstract : To explore the operational role of noncovalent interactions in supramolecular architectures with designed topologies, a series of solid‐state structures of 2‐ and 4‐formylphenyl 4‐substituted benzenesulfonates was investigated. The compounds are 2‐formylphenyl 4‐methylbenzenesulfonate, C14 H12 O4 S, 3a, 2‐formylphenyl 4‐chlorobenzenesulfonate, C13 H9 ClO4 S, 3b, 2‐formylphenyl 4‐bromobenzenesulfonate, C13 H9 BrO4 S, 3c, 4‐formylphenyl 4‐methylbenzenesulfonate, C14 H12 O4 S, 4a, 4‐formylphenyl 4‐chlorobenzenesulfonate, 4b, C13 H9 ClO4 S, and 4‐formylphenyl 4‐bromobenzenesulfonate, C13 H9 BrO4 S, 4c . The title compounds were synthesized under basic conditions from salicylaldehyde/4‐hydroxybenzaldehydes and various aryl sulfonyl chlorides. Remarkably, halogen‐bonding interactions are found to be important to rationalize the solid‐state crystal structures. In particular, the formation of O… X ( X = Cl and Br) and type I X … X halogen‐bonding interactions have been analyzed by means of density functional theory (DFT) calculations and characterized using Bader's theory of `atoms in molecules' and molecular electrostatic potential (MEP) surfaces, confirming the relevance and stabilizing nature of these interactions. They have been compared to antiparallel π‐stacking interactions that are formed between the arylsulfonates.